My encyclopedia of very important science - Davey, Elizabeth; Melmoth, Jonathan; Mills, Andrea (DK Publishing, 2025)
"This beginners' book introduces children to the science all around us. From how a plant makes seeds, and how a caterpillar turns into a butterfly, to how we use friction to warm our hands, and how gravity holds us on the Earth, this book has it covered. Investigate the energy of light and sound, examine the power of electricity and magnets, and inspect the makeup of glass. Then study the strength of plastic and how it can be recycled and reused. Next launch into space and explore the planets of the Solar System and discover why we float in space"--